Heart failure hospitalization reduction and cost savings achieved by improved delivery of effective biventricular pacing: economic implications of the OLE study under the US setting - Hernández-Madrid A; Lu X; Tsintzos SI; Fagan DH; Klepfer RN; Matía R; Chung ES (Dove Medical Press, 2019)
Antonio Hernández-Madrid,1 Xiaoxiao Lu,2 Stelios I Tsintzos,3 Dedra H Fagan,2 Ruth Nicholson Klepfer,2 Roberto Matía,1 Eugene S Chung41Arrhythmia Unit, Cardiology Department, Ramón y Cajal Hospital, Alcalá University, Madrid, Spain; 2Medtronic, plc, Mounds View, MN, USA; 3Medtronic, Tolochenaz, Switzerland; 4The Christ Hospital Heart and Vascular Center, The Lindner Center for Research and Education, Cincinnati, OH, USABackground: The hOLter for Efficacy analysis (OLE) study demonstrated that current device pacing diagnostics overestimate the amount of cardiac resynchronization therapy (CRT) pacing that effectively stimulates the cardiac tissue. Sub-optimal pacing increases mortality, hospitalizations, and associated health-care costs. We sought to estimate the expected number of hospital admissions due to heart failure (HF) and its respective financial impact in patients with maximized effective pacing versus conventional pacing.Methods: A Markov model was developed to project HF hospitalizations and quantify the costs that could be avoided if pacing was maximally effective. OLE data were used to inform the prevalence of ineffective pacing among CRT patients and and average loss of pacing by causes. Adaptive CRT trial data quantified the reduction in underlying hospitalization risk by increasing effective pacing delivered. Survival was informed by a meta-analysis of 5 randomized clinical trials. Costs were analyzed from a US payer perspective.Results: Projected average hospitalizations totaled 4.58 over a lifetime horizon for CRT patients with conventional pacing. Maximizing effective pacing delivery was projected to avoid 1.83 HF admissions/patient over the lifetime. This equates to a savings of 40% (US$22,802) compared with conventional pacing from the Medicare perspective. In a sensitivity analysis, CRT with effective pacing was projected to provide cost savings in all scenarios.Conclusions: Maximized effective pacing leads to a lower number of HF hospitalizations, thus allowing significant cost offsets in the US setting.Keywords: heart failure, ventricular pacing, effective pacing, hospitalization reduction, cost savings